Determinan stunting pada balita usia 6–59 bulan di Kecamatan Trienggadeng, Pidie Jaya, Aceh - Ramadhaniah Ramadhaniah; Aryandi Darwis; Ayu Rafiony; Suaebah Suaebah (Poltekkes Kemenkes Aceh, 2026)
Background: Stunting is a chronic nutritional problem in Indonesia. The Trienggadeng District of Pidie Jaya requires locally specific evidence on breastfeeding practices, immunization, colostrum administration, and birth weight to support targeted prevention.Objectives: To identify factors associated with stunting among children aged 6–59 months in Trienggadeng District, Pidie Jaya, Aceh.Methods: A case-control study was conducted from May to August 2022 in 17 villages selected using cluster sampling. The study included 214 children (107 cases and 107 controls). Data were collected through anthropometric screening and interviews using a standardized questionnaire and analyzed using univariate and bivariate methods.Results: Children who were not exclusively breastfed (OR = 16.85; 95% CI: 8.07–35.74), did not receive early initiation of breastfeeding (OR = 8.16; 95% CI: 3.97–17.33), had incomplete immunization (OR = 14.24; 95% CI: 7.08–29.71), did not receive colostrum (OR = 3.27; 95% CI: 1.78–6.03), or had low birth weight (OR = 19.09; 95% CI: 5.64–99.24) had higher odds of stunting (all p = 0.0001). Low birth weight showed the largest crude OR value.Conclusion: Exclusive breastfeeding, early initiation of breastfeeding, immunization status, colostrum administration, and birth weight were associated with stunting. Prevention should strengthen antenatal care, low birth weight prevention, breastfeeding support, immunization coverage, and early life nutrition services.